Synovial Fluid Markers and Extracellular Vesicles in Rheumatoid Arthritis - Veronika Smolinska; Daniela Klimova; Lubos Danisovic; Stefan Harsanyi (Medicina)
In recent years, numerous potential prognostic biomarkers for rheumatoid arthritis (RA) have been investigated. Despite these advancements, clinical practice primarily relies on autoantibody tests—for rheumatoid factor (RF) and anti-citrullinated protein antibody (anti-CCP)—alongside inflammatory markers, such as the erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Expanding the repertoire of diagnostic and therapeutic biomarkers is critical for improving clinical outcomes in RA. Emerging evidence highlights the significance of synovial fluid biomarkers, including aggrecan, matrix metalloproteinases, glucosyl-galactosyl-pyridinoline, hyaluronic acid, S100 proteins, calprotectin, and various cytokines, as well as immunological markers. Additionally, specific components of extracellular vesicles, such as non-coding RNAs, heat shock proteins, and lipids, are gaining attention. This review focuses on molecular markers found in synovial fluid and extracellular vesicles, excluding clinical and imaging biomarkers, and explores their potential applications in the diagnosis and management of RA.